2009
DOI: 10.1371/journal.pone.0005329
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characterization of Human Mammary Stem/Progenitor Cells in Long Term Culture

Abstract: BackgroundCancer stem cells exhibit close resemblance to normal stem cells in phenotype as well as function. Hence, studying normal stem cell behavior is important in understanding cancer pathogenesis. It has recently been shown that human breast stem cells can be enriched in suspension cultures as mammospheres. However, little is known about the behavior of these cells in long-term cultures. Since extensive self-renewal potential is the hallmark of stem cells, we undertook a detailed phenotypic and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 51 publications
4
79
0
Order By: Relevance
“…In keeping with this, a reverse transcriptase-PCR (RT-PCR) analysis comparing HMECs grown as monolayers versus mammospheres revealed an increased expression of stemness-related genes (such as, Bmi1, Nanog, Lef1, Gli1, Notch1, Hes1, HeyL and CD44), and epithelial to mesenchymal transition (EMT) markers associated with stemness (such as, Vimentin, N-cadherin, FN1, Snai1 and Slug1) (Mani et al, 2008) in mammospheres ( Figure 1a). We had previously demonstrated that the lifespan of normal mammospheres in vitro is limited to four passages (Dey et al, 2009), thereby limiting their utility for studying mammary stem cell biology. Therefore, we sought to generate immortalized breast cell lines that retain long-term stem-like properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with this, a reverse transcriptase-PCR (RT-PCR) analysis comparing HMECs grown as monolayers versus mammospheres revealed an increased expression of stemness-related genes (such as, Bmi1, Nanog, Lef1, Gli1, Notch1, Hes1, HeyL and CD44), and epithelial to mesenchymal transition (EMT) markers associated with stemness (such as, Vimentin, N-cadherin, FN1, Snai1 and Slug1) (Mani et al, 2008) in mammospheres ( Figure 1a). We had previously demonstrated that the lifespan of normal mammospheres in vitro is limited to four passages (Dey et al, 2009), thereby limiting their utility for studying mammary stem cell biology. Therefore, we sought to generate immortalized breast cell lines that retain long-term stem-like properties.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that normal mammospheres can be passaged in suspension for a maximum of four passages, beyond which they fail to generate spheres and largely undergo senescence (Dey et al, 2009). On the other hand, immortalized mammary cell line such as HMLEs (Elenbaas et al, 2001) can be cultured in vitro for prolonged periods; however, they lack the ability to generate mammospheres (Mani et al, 2008;Morel et al, 2008), indicating the lack of stem-like properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary evidence also suggests that it can affect the primary breast tumor cells. Inhibition of Notch signaling leads to reduction in mammosphere-forming capacity (19,41,43), hallmark of putative stem-like cell subpopulation. The mAb 602.101 inhibited cell proliferation and mammosphere formation up to 3 generations in cell lines, as well as, the primary tumor cells, suggesting a strong therapeutic prospect of this antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Mammosphere assay MCF-7, MDA-MB-231 (5 Â 10 4 cells per well), and the enzymatically dissociated single-cell suspensions (2.5 Â 10 5 cells per well) of the primary breast cancer tissues were seeded in a serum-free DMEM-F12 medium with growth factors in a semisolid medium containing methylcellulose as described earlier (19,41). Effect of anti-Notch1 antibodies on sphere-forming efficiency of these cells was assessed by incubating the cells with or without antibodies (10 mg/mL) and culturing for 1 week, replenishing the antibody every fourth day.…”
Section: Collection and Processing Of Primary Breast Cancer Tissuementioning
confidence: 99%